Peran Teknologi Baru, Transparansi Data Keuangan, dan Kualitas Auditor dalam Tata Kelola Keuangan - Riyanto Tri Wijaya, Juli; Bakhtiar, Syamsul; Manurung, Muhammad Rizqi Alriansyah (UMSurabaya Publishing, 2025)
This study examines the effects of new technologies, financial data transparency, and auditor quality on financial governance in the digital era. Using a quantitative approach, data were collected from 30 auditors across sectors through a structured questionnaire and analyzed with SmartPLS 4.0. The results show that all three variables significantly influence financial governance, with new technologies having the strongest positive impact. Financial data transparency also contributes positively, while auditor quality shows a significant but negative effect, suggesting potential challenges in audit independence or practices. This result indicates that stronger auditor quality, while essential, may initially reveal governance deficiencies, explaining its significant negative effect.. The model demonstrates strong explanatory power (R² = 0.99) and reliable validity indicators, confirming result robustness. The study concludes that effective financial governance requires integrating digital tools, transparent reporting, and competent auditors. It recommends that audit firms and regulators invest in digital infrastructure, improve auditor skills, and strengthen transparency to enhance governance frameworks. These findings offer practical insights for advancing financial governance in the digital era.